MANAJEMEN PENGADAAN DAN PENGEMBANGAN KINERJA KEPALA SEKOLAH: Studi Deskriptif di Lingkungan Dinas Pendidikan Kabupaten Serang - Nugrahajaya, Asep (2012)
MANAJEMEN PENGADAAN DAN PENGEMBANGAN KINERJA KEPALA SEKOLAH: Studi Deskriptif di Lingkungan Dinas Pendidikan Kabupaten SerangThe focus of the research on the dissertation is "management of school principal performance development". This becomes the thinking base that school principal is the education leader who has responsibility to carry out education at school, to bring best school fulfil its "customers". The successful indicators of school principal can be seen how far the vision, mission, and strategies are carried out, and all participants are participated. The outcome mentioned is gained. Therefore, increasing and development school is depending on the school principal's attention and competitions to run the vision, mission and strategy can be existence. In general, the research of this dissertation is to get illustration about the effort of developing the principal's skill in managing the elementary school. The specific goals of the research are: 1. To get illustration about the Elementary School Principal Recruitment in Serang District 2. To get illustration about the process of selection of Elementary School Principal in Serang District 3. To study the performance development strategy of Elementary School Principal's leadership in Serang District 4. To analyse the model of performance development strategy of Elementary School Principal's leadership to increase the quality of education effective and efficiently. Method used in the research is evaluative research, the research to define the worth from education practice. Whereas the approach is qualitative, and sampling data technique done by interviewing, document study and observation. Specifically, from the research we can conclude as follow: 1. The recruitment of Elementary School Principal in less integrated with the effort of quality education development as a whole, because it is based on seniority and less performance quality based, so that the development condition in elementary school is not optimum. 2. Decision of teacher becomes school principal is not based on school organization need, but, based on fulfilling an inexistent of school principal, so that it is more natural than planned as the general policy of education quality in Serang District. This condition shows that the change of school principal leadership always waits the inexistent of school principal without seeing the school organization need to develop education quality. This condition makes Click here to buy ABBYY PDF Transformer 2.0 www.ABBYY.com Click here to buy ABBYY PDF Transformer 2.0 www.ABBYY.com the lower performance of elementary school principal to manage high quality education. 3. The development strategy of elementary school principal ability shows less planed and, is not participated by the people who know well about school organization management, such as, supervisors. It causes less developed school principal, caused of education and training is not based on real need. There are desperations between training and need, moreover, less training due to limited finance. 4. The model of strategy of leadership skill development is given only in the form of education and training as technique guidance for elementary school principal candidates where the activities have not well-planned and systematised, so the result is less optimum. It is because the training substances focused on administrative aspect, not on the increase of organization's comprehension as a system. Because of the important of school principal role, to increase education quality, there are things that become recommendation and need to be done everyone to make strategic, effective, systemic and systematic. 1. To the Local government, Serang district, It is hoped to give better attention to increase school principal performance including elementary school, by allocating more fund so that the implementation of performance development can run well and continuously. 2. To the Education Fair, Serang District, Need accurate strategy and based on quality management on developing school principal leadership performance through planning of school principal leadership as inseparable unit. Besides that, supervisor and sub district education (UPTD) participation is a must, and become integrated system on recruitment, placement, and competencies development to get effective school principal leadership. 3. To "UPTD" and elementary supervisor. It needs more substantive effort to help school principal recruitment, not only formal aspect but also the substance aspect of leadership competencies to fulfil organization need. Therefore, effort to increase school principal leadership performance fulfils the need of school principal and organization. 4. To the school principal. Grow the self-conscious the importance of the role as school leader through self-development on education and leadership so that, continuously, it becomes self-need to work as teacher profession and as school principal.